Kroppsøvingslæreres credo - deres refleksjoner i lys av van Manens begrep om pedagogisk takt - Ove Olsen Sæle; Bjørg Oddrun Hallås; Gunn Helene Engelsrud (Dalarna university, 2023)
The article examines what teachers, who are students in further education, teacher specialists in physical education, write in their pedagogic creed reflections related to what they are passionate about, and believe in, in their professional practice. The study is part of a larger follow-up research at a University in Norway, and the material used in this article are texts written in connection with a work requirement added to the start of studies in autumn 2019. The texts, from 12 informants, have been interpreted in the light of van Manen's concept pedagogical tact. Key findings are that the physical education teachers are particularly concerned with their students, and the importance of seeing the individual student, as well as being a role model for them. We have also seen that the creed texts often contain a political ideological language, and a less personal, authentic language, and that many of the pedagogic creeds express their own interests and traditional discourses in the subject.